The impact of high-risk and chronic opioid use among commercially insured endometriosis patients on health care resource utilization and costs in the United States. (November 2020) - Estes, Stephanie J; Soliman, Ahmed M; Zivkovic, Marko; Chopra, Divyan; Zhu, Xuelian
Objectives: Evaluate all-cause and endometriosis-related health care resource utilization and costs among newly diagnosed endometriosis patients with high-risk versus low-risk opioid use or patients with chronic versus non-chronic opioid use. Methods: A retrospective analysis of IBM MarketScan ® Commercial Claims data from 2009 to 2018 was performed for females aged 18 to 49 with newly diagnosed endometriosis (International Classification of Diseases, Ninth Edition code: 617.xx; International Classification of Diseases, Tenth Edition code: N80.xx). Two sub-cohorts were identified: high-risk (⩾1 day with ⩾90 morphine milligram equivalents per day or ⩾1-day concomitant benzodiazepine use) or chronic opioid utilization (⩾90-day supply prescribed or ⩾10 opioid prescriptions). High-risk or chronic utilization was evaluated during the 12-month assessment period after the index date. Index date was the first opioid prescription within 12 months following endometriosis diagnosis. All outcomes were assessed over 12-month post-assessment period while adjusting for demographic and clinical characteristics. Results: Out of 61, 019 patients identified, 18, 239 had high-risk opioid use and 5001 chronic opioid use. Health care resource utilization drivers were outpatient visits and pharmacy fills, which were higher among high-risk versus low-risk patients (outpatient visits: 17.49 vs 15.51; pharmacy fills: 19.58 vs 16.88, p < 0.0001). Chronic opioid users had a higher number of outpatient visits (19.53 vs 15.00, p < 0.0001) and pharmacy fills (23.18 vs 16.43, p < 0.0001) compared to non-chronic opioid users. High-risk opioid users had significantly higher all-cause health care costs compared to low-risk opioid users (US16, 377 vs US13, 153; p < 0.0001). Chronic opioid users also had significantly higher all-cause health care costs compared to non-chronic opioid users (US20, 930 vs US12, 272; p < 0.0001). Similar patterns were observed among endometriosis-related HCRU, except pharmacy fills among high-risk and chronic sub-cohorts. Conclusion: This analysis demonstrates significantly higher all-cause and endometriosis-related health care resource utilization and total costs for high-risk opioid users compared to low-risk opioid users among newly diagnosed endometriosis patients over 1 year. Similar trends were observed for comparing chronic opioid users with non-chronic opioid users, except for endometriosis-related pharmacy fills and associated costs.